Optimalisasi Pengolahan Kue Dari Ubi Jalar Orange Dan Ungu Menggunakan Pemrograman Linier - Gabrilia Domita Sari; Vivi Melati; Maria Blandina Iju; Teodard Rico Santoso; Jontua Parningotan Manurung; Jhon Roy; Dudy Effendy (Program Studi Ekonomi Pembangunan Fakultas Ekononomi Universitas Simalungun, 2022)
Small and medium businesses (SMBs) have considerable potential to be developed. The sweet bingke cake, the ude lala stall, which is located on Jalan Tanjung Raya II, the capital city of Pontianak, is one of the places to develop small and medium businesses. Poor management will produce products that are not optimal and will have an impact on the profits obtained are not optimal. The purpose of this study is to maximize profits for UKM cake bingke in the city of Pontianak using linear programming. From the calculation results, it was found that to obtain the maximum profit of 500000 per day, Ude Lala produced 0 times of orange sweet potato, 1.67 times of purple sweet potato.